Myocardial injury after non-cardiac surgery: A prevalence study - Coetzee, Ettienne (Department of Anaesthesia and Perioperative Medicine, 2019)
Background Worldwide, the number of patients suffering from surgical complications account for a significant burden on healthcare systems. Myocardial injury after non-cardiac surgery (MINS) is a new entity that has recently been identified as an independent risk factor associated with 30-day all-cause mortality. The risk of death increases approximately 10 fold following MINS in the perioperative period. Diagnosing myocardial injury in nonsurgical patients often relies on specific symptomatology and clinical findings combined with special investigations. However, in surgical patients, more than 80% of patients with postoperative myocardial injury will be asymptomatic, and hence the majority of diagnoses will be missed. Studies identifying the prevalence and risk factors for MINS have been conducted in countries with a different surgical population to South Africa. The primary outcome of this study was to investigate the prevalence of MINS after non-cardiac, elective, elevated risk surgery in South Africa. Methods Patients undergoing elevated risk, elective, non-cardiac surgery ≥ 45 years of age were enrolled via convenience sampling. The new 5th generation, high sensitivity cardiac troponin T (hscTnT) blood test was used to identify MINS. Blood samples were taken between 24 to 72 hours after surgery. Exclusion criteria included patients with known renal disease, a recent cardiac event, pulmonary embolism or sepsis. Results A total of 244 patients were included in the study. The prevalence of MINS was 4.9% (95% CI 2.2-7.6) which was not significantly different (p=0.078) to reports from international prospective observational studies. Conclusion Elective, elevated risk surgical patients in South Africa have a similar incidence of MINS when compared to patients from international studies. As the risk profile of South African patients is significantly lower than other similar international observational studies, it is possible that the prevalence of MINS is more common in South Africa, when patients are adjusted for cardiovascular risk profile. The burden of MINS on public health morbidity is therefore likely to be proportionally more in South Africa when compared to international reports. This may suggest that the calibration of international cardiovascular risk prediction models is incorrect for South African patients, or there are confounding comorbidities which should be included in South African cardiovascular risk prediction models. Larger studies are required to confirm this hypothesis however, and should also aim to address the need for appropriate cardiovascular risk predicting models in South Africa, to ensure timeous identification of patients at risk of MINS.